Causal Effects of Circulating Cytokines on the Risk of Psoriasis Vulgaris: A Mendelian Randomization Study - Zhao, Pan; Zhang, Jing; Liu, Biyong; Tang, Yufei; Wang, Lei; Wang, Guifeng; Wu, Huihui; Yang, Chengwei; Li, Xuemei; Li, Bo (Frontiers in Genetics, 2022)
Background: Psoriasis vulgaris is an inflammatory skin disease. Observational studies have shown associations between circulating cytokine levels and psoriasis vulgaris. But the causal relationship between circulating cytokine and psoriasis vulgaris remains elusive. Methods: To assess the causal effects of cytokine levels on the risk of psoriasis vulgaris and vice versa, we performed a two-sample Mendelian randomization (MR) study by using the inverse-variance weighted (IVW), weighted median, and Mendelian randomization pleiotropy residual sum and outlier (MR-PRESSO) in genome-wide association summary statistics of 41 circulating cytokines in up to 8,293 individuals and psoriasis vulgaris in 399,883 individuals. Results: We identified that increasing RANTES level induced an elevated risk of psoriasis vulgaris in IVW (β=0.33, S.E.=0.12, P=0.006). This causal effect showed consistency across the weighted median (β=0.35, S.E.=0.15, P=0.022) and MR-PRESSO method (β=0.33, S.E.=0.11, P=0.028). Conclusions: Our results suggest a potential causal effect of elevated RANTES concentration on the increased risk of psoriasis vulgaris.